2009
DOI: 10.1002/adma.200803431
|View full text |Cite
|
Sign up to set email alerts
|

High‐Pressure, High‐Temperature Formation of Phase‐Pure Monoclinic Zirconia Nanocrystals Studied by Time‐Resolved in situ Synchrotron X‐Ray Diffraction

Abstract: Zirconia is one of the most studied metal oxides due to the important mechanical, thermal, electrical and catalytic properties and the many applications they offer. [1] In virtually all applications of zirconia, the key challenge is to control the crystal phase, morphology, and stoichiometry in order to tailor the specific targeted properties. The thermodynamically stable crystal phase of bulk zirconia is the monoclinic structure, which transforms into the tetragonal phase at 1175 8C. The tetragonal phase can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 22 publications
3
58
0
Order By: Relevance
“…[249] Generally, monoclinic ZrO 2 has been known as the thermodynamically stable bulk phase, whereas the metastable tetragonal ZrO 2 is stabilized in nanoparticles below a critical size limit of 30 nm as a result of the lower surface energy. However, for the gels under investigation, the local structure of did not bear a resemblance to any of these established modifications and they were subsequently transformed into monoclinic ZrO 2 particles with diameters of only few nanometers.…”
Section: Reviews 844mentioning
confidence: 99%
“…[249] Generally, monoclinic ZrO 2 has been known as the thermodynamically stable bulk phase, whereas the metastable tetragonal ZrO 2 is stabilized in nanoparticles below a critical size limit of 30 nm as a result of the lower surface energy. However, for the gels under investigation, the local structure of did not bear a resemblance to any of these established modifications and they were subsequently transformed into monoclinic ZrO 2 particles with diameters of only few nanometers.…”
Section: Reviews 844mentioning
confidence: 99%
“…When different precursors are used for hydrothermal synthesis, it is often observed that the product has specific characteristics, e.g. [9][10][11][12][13] In particular, a few studies have been devoted to the study of TiO 2 crystallization and growth by in situ synchrotron PXRD under solvothermal, hydrothermal or sol-gel conditions. However, the processes occurring during the formation of nanoparticles are not well understood, and this, to a large extent, prevents rational synthesis of new materials.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, high energy synchrotron X-rays represent such an ideal class of probes because they can efficiently penetrate liquid electrolytes. The corresponding timeresolved techniques (such as small-angle X-ray scattering [138][139], X-ray absorption spectroscopy [140][141], wide-angle X-ray scattering [142][143][144][145]) show the potential for real-time monitoring nanoparticle growth in liquid media. Continuous efforts in establishing robust, sensitive, high time-resolution, high-energy X-ray techniques may represent a research direction for understanding the complicated nanoparticles growth process in solution phase and providing valuable knowledge to improve the quality of nanoparticles.…”
Section: Discussionmentioning
confidence: 99%